Impact of political instability on 1948-Palestinian shoppers’ satisfaction: Palestinian tourist destination as a case study - Jafar Abahre; Hussein Al-Rimmawi; Loai Abu Raida; Mohammad Alkhateeb; Wasim Bishawi; Sameer Mahmoud; Akram Suleiman; Zuheir N. Khlaif (Heliyon, 2023)
This study examines tourist satisfaction and its relationship with demographic variables in Nablus, Palestine. Two hundred two tourists were surveyed using a structured questionnaire to collect data on their satisfaction level and demographic information. The results reveal that the overall tourist satisfaction level in Nablus is high. However, significant differences in satisfaction were found based on gender, education level, number of family members, occupation, and income. The study highlights the importance of considering demographic factors in shaping visitor satisfaction and tailoring tourism services to meet the needs and preferences of diverse clients. The findings also shed light on the negative impact of tourist blackmailing, which is the exploitation of tourists by various stakeholders, and the role of positive perceptions of the destination in attracting tourists and mitigating the impact of security threats. The study provides valuable insights for tourism service providers and stakeholders in promoting sustainable and competitive tourism in Nablus and the West Bank region.